2019
DOI: 10.1039/c9ay01580a
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic detection in water using microfluidic detection systems based on the leucomalachite green method

Abstract: This work describes the first use of microfluidic detection technology for arsenic detection in water using leucomalachite green dye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Lace and co-workers developed a method for microfluidic detection of arsenic in water using leucomalachite green dye [65,66]. The dye reacted with arsenic to produce a green coloured complex with peak absorption (λ max ) at 617 nm.…”
Section: Absorbance Based Detectionmentioning
confidence: 99%
“…Lace and co-workers developed a method for microfluidic detection of arsenic in water using leucomalachite green dye [65,66]. The dye reacted with arsenic to produce a green coloured complex with peak absorption (λ max ) at 617 nm.…”
Section: Absorbance Based Detectionmentioning
confidence: 99%
“…Similar enzyme inhibition by copper metal ions has been reported by Male and coauthors [39] where he has observed its interference in different levels. Lace and coauthors [5] has reported that Fe 2+ ions above 0.1 mg -1 interfere with As 3+ monitoring using the microfluidic detection system.…”
Section: Effect Of Interfering Substancesmentioning
confidence: 99%
“…[4]. Exposure to arsenic can lead to various health concerns including cardiovascular diseases [5], skin lesions [6], arsenicosis [7], various types of cancer and mutagenic effects, hematological side effects [8], hyperkeratosis [9], and many more disorders. Arsenic is registered as priority toxic element under the European Directive on Environmental Quality Standards due to its toxicity [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, both of them require tedious sample preparation and pretreatment, expensive equipment, and professional personnel, making them insuitable in applications for autonomous, in situ, and continuous monitoring of heavy metals. In this case, ocean monitoring sensors based on colorimetric, fluorescent, and chemiluminescent methods appear as promising technologies due to the high sensitivity and feasibility, versatility, and reproducibility [84][85][86][87][88][89][90][91][92][93][94][95], and all of these methods have been truly applied for online analysis of heavy metals in seawater.…”
Section: Heavy Metalsmentioning
confidence: 99%
“…With this portable device, 12 samples of Fe(II) and 6 samples of Mn could be analyzed per hour with LODs of 27 nM and 28 nM, and precisions of 2.1% and 2.4% (n = 19), respectively. Lace et al reported an innovative optofluidics system for monitoring of arsenic in water with the leucomalachite green dye method [91]. The principle involves the reactions of arsenic and potassium iodate under acidic conditions, and leucomalachite green is oxidized to malachite green by the liberated iodine, producing a green color with an absorption peak at 617 nm.…”
Section: Heavy Metalsmentioning
confidence: 99%